2012
DOI: 10.1007/s00167-012-2219-8
|View full text |Cite
|
Sign up to set email alerts
|

Treatment for insertional Achilles tendinopathy: a systematic review

Abstract: Despite differences in outcome and complication ratio, the patient satisfaction is high in all surgical studies. It is not possible to draw conclusions regarding the best surgical treatment for insertional Achilles tendinopathy. ESWT seems effective in patients with non-calcified insertional Achilles tendinopathy. Although both eccentric exercises resulted in a decrease in VAS score, full range of motion eccentric exercises shows a low patient satisfaction compared to floor level exercises and other conservati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
102
2
11

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(118 citation statements)
references
References 52 publications
(143 reference statements)
3
102
2
11
Order By: Relevance
“…Many research studies and a review article published in 2013 46 support the role of ESWT for treatment of IAT, whereas at our knowledge there is no evidence in the literature about the use of PRP injections for this tendinopathy. In 2006, Furia 36 published a case control study about the effectiveness of ESWT on IAT.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Many research studies and a review article published in 2013 46 support the role of ESWT for treatment of IAT, whereas at our knowledge there is no evidence in the literature about the use of PRP injections for this tendinopathy. In 2006, Furia 36 published a case control study about the effectiveness of ESWT on IAT.…”
Section: Discussionmentioning
confidence: 97%
“…Basic science studies about PRP mechanism action show that growth factors in PRP significantly enhance the healing of tendon injuries such as tendinopathy 45 . In scientific literature, there is no evidence about the most effective non-surgical intervention for IAT 46 . The aim of this retrospective study is to analyse the results obtained by two treatments (ESWT and PRP) in physically active patients with chronic IAT focusing on effectiveness, pain reduction, functional recovery and satisfaction in time span of six months after end of the treatments.…”
Section: Conservative Treatment For Insertional Achilles Tendinopathymentioning
confidence: 99%
“…17 Recently, ESWs have been introduced as an effective treatment against Achilles tendinosis. Wiegerinck et al 18 conducted a systematic review of the common therapies for insertional Achilles tendinopathy and concluded that ESWs were used in most of the searched literature and that, overall, 49 of 64 recruited patients (77%) with Achilles tendinopathy were satisfied with the clinical outcomes after ESW therapy, suggesting that ESW therapy was superior to wait-and-see and the eccentric training regimen in terms of clinical efficacy and safety. In addition, it is easily accepted by most patients because it does not require surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is easily accepted by most patients because it does not require surgery. 18 Maffulli et al 19 performed ESW on 127 patients diagnosed as having Achilles tendinitis, and the results showed a 2-month effective rate of 47%, which increased to 73% after 1 year and 76% at the end of 2 years of treatment. Furia 20 also conducted a 1-year follow-up study in patients with insertional Achilles tendinosis and also achieved high efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…7 Conservative care has been shown to be successful in treating Achilles tendinopathies. [8][9][10][11] Conservative treatments may include rest from activity, iontophoresis, foot orthoses, stretching, and eccentric exercises. 12 Eccentric training, in particular, has repeatedly shown positive outcomes when used to treat athletic individuals with mid-portion Achilles tendinopathy.…”
Section: Achilles Tendinopathy Case Studymentioning
confidence: 99%